Evaluation of radiation-induced soft error in majority voters designed in 7 nm FinFET technology. (September 2017) - de Aguiar, Y.Q.; Artola, L.; Hubert, G.; Meinhardt, C.; Kastensmidt, F.L.; Reis, R.A.L.
Abstract: Radiation-induced soft error is an ever-increasing concern in the microelectronic industry in order to provide reliable VLSI systems at advanced technology nodes. Most of the redundancy-based methodologies adopt majority voters to ensure the fault masking. This paper presents a comparative analysis of different majority voter designs in 7 nm FinFET under radiation effects. The MUSCA SEP3 tool is used to estimate the SER of each circuit. Results show that NOR voter is less sensitive than the NAND voter. However, the SET pulse width is larger for the NOR voter than NAND voter. Highlights: Radiation-induced soft errors are an ever-increasing concern to reliable VLSI systems. Most of the redundancy-based methods adopt majority voters to ensure fault masking. This paper investigates the radiation effects on different majority voters in 7 nm FinFET. NOR voter is less sensitive than NAND voter. SET pulse width is larger for NOR voter than NAND voter.